Combining Suppression of Stemness with Lineage-Specific Induction Leads to Conversion of Pluripotent Cells into Functional Neurons. Issue 11 (19th November 2015) - Halder, Debasish; Chang, Gyeong-Eon; De, Debojyoti; Cheong, Eunji; Kim, Kyeong Kyu; Shin, Injae
Summary: Sox2 is a key player in the maintenance of pluripotency and stemness, and thus inhibition of its function would abrogate the stemness of pluripotent cells and induce differentiation into several types of cells. Herein we describe a strategy that relies on a combination of Sox2 inhibition with lineage-specific induction to promote efficient and selective differentiation of pluripotent P19 cells into neurons. When P19 cells transduced with Skp protein, an inhibitor of Sox2, are incubated with a neurogenesis inducer, the cells are selectively converted into neurons that generate depolarization-induced sodium currents and action potentials. This finding indicates that the differentiated neurons are electrophysiologically active. Signaling pathway studies lead us to conclude that a combination of Skp with the neurogenesis inducer enhances neurogenesis in P19 cells by activating Wnt and Notch pathways. The present differentiation protocol could be valuable to selectively generate functionally active neurons from pluripotent cells. Graphical Abstract: Highlights: Skp protein suppresses stemness and induces early differentiation Sequential treatment of Skp and Nz/Nzl leads to selective neuronal differentiation Sequential treatment of Skp and Nz/Nzl produces electrophysiologically active neurons Treatment of Skp and Nz/Nzl enhances neurogenesis by activating Wnt and Notch pathways Abstract : Halder et al. demonstrated that a combination of Sox2 inhibition with lineage-specific induction led to efficient and selective differentiation of pluripotent P19 cells into neurons. Differentiated neuronal cells exhibited voltage-dependent inward and outward sodium currents and depolarization-induced action potentials.